Comparative analysis of competencies for integrating climate action education between urban and rural primary English teachers in Jiangsu Province, China - Wu, Xiaowei; Syed Abdullah, Sharifah Intan Sharina (Human Resources Management Academic Research Society (HRMARS), 2024)
Climate change represents a significant challenge for humanity, with climate action being the 13th goal of the Sustainable Development Goals (SDGs). Education plays a crucial role in addressing this issue, particularly for primary school students, who are at a pivotal stage for climate change education. This study focuses on Jiangsu Province, where disparities in educational resources between urban and rural areas have led to differences in the quality of climate change education. Using a quantitative research method, a questionnaire survey was conducted with 409 primary English teachers in Jiangsu Province to compare and analyze their climate action skills, employing pedagogical content knowledge (PCK) as a framework. The data analysis revealed a significant difference in the ability of urban and rural teachers to integrate climate action into their teaching. Urban teachers demonstrated higher competency, which is attributed to greater professional development opportunities and better educational resources. In contrast, rural teachers faced challenges such as limited training and fewer professional development opportunities, which impacted their effectiveness in integrating climate action. To address these disparities and improve the quality of climate change education, the study suggests the need for balancing educational resources between urban and rural areas and developing targeted policies. These findings offer valuable insights for promoting equity in climate change education in Jiangsu Province and similar regions, and further research could explore the impact of specific policy interventions on reducing these disparities.